2016
DOI: 10.1080/10962247.2016.1188865
|View full text |Cite
|
Sign up to set email alerts
|

Odor composition analysis and odor indicator selection during sewage sludge composting

Abstract: On the basis of total temperature increase, normal dehydration, and maturity, the odor compositions of surface and internal piles in a well-run sewage sludge compost plant were analyzed using gas chromatography–mass spectrometry with a liquid nitrogen cooling system and a portable odor detector. Approximately 80 types of substances were detected, including 2 volatile inorganic compounds, 4 sulfur organic compounds, 16 benzenes, 27 alkanes, 15 alkenes, and 19 halogenated compounds. Most pollutants were mainly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 34 publications
5
33
0
Order By: Relevance
“…The exact composition of the mixture was slightly different than in these studies-in addition to 35% sawdust, there was still 5% straw, but also a 45% higher total weight and air-flow that was over 20% greater (which had a detrimental effect on the release of ammonia). Other studies have also shown high ammonia emissions during high temperatures, while the peak of NH 3 emissions coincided with the maximum temperature and oxygen uptake rate [48,[61][62][63].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The exact composition of the mixture was slightly different than in these studies-in addition to 35% sawdust, there was still 5% straw, but also a 45% higher total weight and air-flow that was over 20% greater (which had a detrimental effect on the release of ammonia). Other studies have also shown high ammonia emissions during high temperatures, while the peak of NH 3 emissions coincided with the maximum temperature and oxygen uptake rate [48,[61][62][63].…”
Section: Resultsmentioning
confidence: 91%
“…Energies 2020, 13, x FOR PEER REVIEW 8 of 13 total weight and air-flow that was over 20% greater (which had a detrimental effect on the release of ammonia). Other studies have also shown high ammonia emissions during high temperatures, while the peak of NH3 emissions coincided with the maximum temperature and oxygen uptake rate [48,[61][62][63]. However, for a better comparison of ammonia losses, it was decided that we would calculate NH3 emission from 1 kg of sewage sludge that was initially used for composting (ammonia emission from straw was negligible).…”
Section: Resultsmentioning
confidence: 99%
“…Composting is a complex biochemical process, wherein the components of produced gases are complicated, and predominantly include ammonia, hydrogen sulfide, and water, as well as mercaptan and thioether [ 32 ]. To ensure the measurement accuracy of the oxygen-monitoring equipment, it was placed in a gas environment with ammonia, hydrogen sulfide, and water.…”
Section: Resultsmentioning
confidence: 99%
“…Due to population density, location and concentration of odour sources and the number of affected individuals, the problem of nuisance mainly concerns urban areas (Pedersen, 2015). Watercourses (Sado-Inamura and Fukushi, 2018) and urban sewerage (García et al, 2017;Zhu et al, 2016) are important sources of urban fragrances. These sources are the subject of studies not only on the chemical composition of liquids but also on the composition of odour emitted by them (Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Watercourses (Sado-Inamura and Fukushi, 2018) and urban sewerage (García et al, 2017;Zhu et al, 2016) are important sources of urban fragrances. These sources are the subject of studies not only on the chemical composition of liquids but also on the composition of odour emitted by them (Zhu et al, 2016). Additional sources of smell in urban areas are increasingly being fumes (Cernansky, 1983), biomass (Freiberg et al, 2018) or fragrances from closed surface equipment, such as offices, which may affect the quality of work and health of employees (Wypych, 2017), and fragrances from landfills or composting plants.…”
Section: Introductionmentioning
confidence: 99%